Fintech adoption: Its determinants and organizational benefits in Indonesia - Dekar Urumsah; Rintan Falah Ispridevi; Aris Nurherwening; Wirawan Hardinto (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
Financial Technology (Fintech) has become an essential issue in the past few years, especially for the companies that offer the products/services that require payment. This research explores the factors which drive companies to adopt fintech - risk perception, cost perception, organizational readiness, top management support, knowledge of information technology, customer pressure, and competitive pressure - and the benefits of its adoption. This research distributed questionnaires using purposive sampling method to the employees working in the companies adopting Fintech. There were 195 questionnaires analyzed using SEM-PLS. This research indicates that customer pressure, competitive pressure, organizational readiness, top management support, and knowledge of information technology have significant influences on Fintech adoption. However, risk perception and cost perception do not significantly affect Fintech adoption. Fintech adoption has a significant effect on organizational benefits. Companies can use this research to find the opportunities and risks when they adopt fintech in order to improve on innovating and maximize customers and partners’ satisfactions.